التمثيل المكاني ثلاثي الأبعاد للمخططات العقارية - زوباري علي; الخليل عمر; عساف حسين (Latakia University Journal -Engineering Sciences Series, 2018)
The currently cadastral system used in Syria is tow dimensional (2D), where all cadastral property and rights are represented 2D by projection their external boundaries on 2D plan (X,Y) without attention to measuring the third dimension (Z or H). This system is no longer able to manage and represent the complexity of the current reality where the representation of the cadastral elements, which are in 3D origin, on a 2D map puts us in front of cases of confusion and ambiguity of the legal and engineering terms. This leads us towards developing the 2D cadastral system to 3D cadastral system, which represents the cadastral property and related rights in 3D. The main aim of this research is designing an up-to-date 3D cadastral digital model, which is based on 3D parcel not on 2D parcel (flat piece of land). To achieve this goal, we initially studied the basics of 3D cadastral modeling, and on the basis of this study it was stressed that this model as well as it is based on 3D parcel, It must represent two basic types of components, namely: the legal components and the physical components, then it was determined the data needed to represent these components in 3D space, then we defining the official sources of this data and later were defined programs and techniques to 3D representation of collected data and finally it was proposed method to visualize the data and connect them with each other. يعتبر النظام العقاري المتبع حالياً في سورية ثنائي البعد، حيث تُمثل الممتلكات والحقوق العقارية بشكل ثنائي البعد عن طريق إسقاط حدودها الخارجية على المستويX,Y))، دون الاهتمام أبداً بقياس البعد الثالث(Z أوH). لم يعد هذا النظام قادراً لتمثيل وإدارة واقعنا الحالي المعقد، حيث أن تمثيل هذه العناصر العقارية، والتي هي في الأصل ثلاثية الأبعاد، بشكل ثنائي الأبعاد يضعنا أمام حالات التباس وغموض من الناحيتين القانونية والهندسية. وهذا يدفعنا باتجاه العمل على تطوير هذا النظام إلى نظام عقاري ثلاثي البعد (3D cadastral system) يقوم بتمثيل وإدارة الملكيات العقارية والحقوق المتعلقة بها في فضاء ثلاثي الأبعاد. إن الهدف الرئيس من هذا البحث هو اقتراح منهجية لتصميم نموذج رقمي لمخطط عقاري ثلاثي الأبعاد قائم على أساس العقار ثلاثي الأبعاد (3D Parcel) وليس على العقار ثنائي البعد (قطعة الأرض المستوية). ولتحقيق هذا الهدف، تم في البداية دراسة أساسيات النمذجة العقارية ثلاثية الأبعاد، وعلى أساسها تم التأكيد على أن هذا النموذج بالإضافة إلى أنه مبني على أساس العقار ثلاثي الأبعاد، فإنه يجب أن يمثل نوعين أساسيين من المكونات هما: المكونات التشريعية أو القانونية(Legal components) والمكونات الفيزيائية(Physical components)، ثم بعد ذلك تم تحديد البيانات اللازمة لتمثيل هذه العناصر المكانية في الفراغ، وتم أيضاً تحديد المصادر الرسمية التي تؤمن هذه البيانات، وبعد ذلك تم تحديد البرامج والتقنيات اللازمة لتمثيل هذه البيانات بشكل ثلاثي الأبعاد، وأخيراً تم اقتراح منهجية لعرض هذه البيانات مكانياً وربطها مع بعضها البعض.